Justice in Health - Burnett, Camille; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Inequities and health disparities are the greatest and most pressing social issues of our time. This book explores public health practice through the critical lens of social and structural justice by examining our approach to health and what it means to be healthy, systemically and structurally. Through recent events, the raw reality of health disparities and inequities have been exposed. These events are earmarked by COVID-19's decimating and disparate impacts on Black and Brown populations during one of the greatest social movements of our time to end racism. Since this very public explosion of intersecting forms of oppression and inequitable suffrage, many have clamored to make sense of it, to reframe our narratives toward action, and re-envision what progress and change could look like. This text is positioned as a tool to help professionals dismantle old ways of thinking while reconstructing new ones that can be more responsive in meeting the realities of today. The author challenges the reader to think about public health more deeply and pragmatically as the space for reconciling solutions to these poignant health issues. This requires the exploration of an ideological shift in how we think of health, how we prepare healthcare providers outside of an antiquated sick care system, and how we prioritize the determinants of health across a re-imagined continuum of care. The scope of this book ranges from a historical and structural examination of our beliefs about health to perceiving a more just system of care where health is intentionally co-created toward this aim. It intentionally explores health along the lines of equity and through the broader lens of the social determinants of health to shed light on the opportunity in this moment that public health creates for health care. Justice in Health is a timely and important resource for healthcare professionals (pre- and post-licensure) and healthcare decision-makers. The book also appeals more widely to instructors, academics, researchers, and students across disciplines of nursing, medicine, public heath, sociology, and social work.
Chapter 1: Collision of Contexts and Conscience -- Chapter 2: Contextualizing and Situating Race and Health in the United States -- Chapter 3: Frameworks for Framing Justice in Health -- Chapter 4: Health Equity and Critical Health Issues -- Chapter 5: Culture of Health -- Chapter 6: Leading Through Just Action -- Chapter 7: Just Health.
Keywords: Public health; Social justice; Medical policy; Race; Social structure; Equality; Public Health; Social Justice; Health Policy; Race and Ethnicity Studies; Social Structure; Global Health; Social Justice